2014
DOI: 10.1042/bsr20140065
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of the human reduced folate carrier as a novel adaptive mechanism in response to folate excess or deficiency

Abstract: The RFC (reduced folate carrier) is the principal mechanism by which folates and clinically used antifolates are delivered to mammalian cells. hRFC (human RFC) is subject to complex transcriptional controls and exists as homo-oligomer. To explore the post-transcriptional regulation of hRFC by exogenous folates, hRFC-null HeLa cells were stably transfected with hRFC under control of a constitutive promoter. hRFC transcripts and the total membrane protein increased with increasing LCV [(6R,S)5-formyl tetrahydrof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Expression of RFC has demonstrated improved response to leucovorin (79). RFC acts like a transcellular ferry by which folates are delivered into cells from the systemic circulation, and RFC-mediated transport of folinic acid (leucovorin) has been well described (80).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of RFC has demonstrated improved response to leucovorin (79). RFC acts like a transcellular ferry by which folates are delivered into cells from the systemic circulation, and RFC-mediated transport of folinic acid (leucovorin) has been well described (80).…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al, (2014), using cultured HeLa cells showed that RFC undergoes posttranscriptional regulation in response to folate excess or deficiency [35]. To our knowledge, our results have shown for the first time that folate concentration in serum cord blood of newborns may be related to the expression of FOLR1 in human placentas.…”
Section: Discussionsupporting
confidence: 50%
“…As far as mRNA stability of folate transporters is concerned, no change in mRNA half life of PCFT, RFC, and FR was observed on ethanol exposure; however, FD treatment resulted in decrease in half life of PCFT and RFC from 4.9 to 3 h and from 2.6 to 1.6 h, respectively, without affecting FR. Similar study conducted on HeLa cells has reported a significant reduction in turnover of hRFC transcripts on decreasing concentration of 5-formyl tetrahydrofolate (leucovorin) [46]. This seems to be some kind of homeostatic mechanism in order to control the expression of folate transporters in conditions of FD, and it is also transporter specific.…”
Section: Discussionmentioning
confidence: 82%